Graft-versus-leukaemia effect post fludarabine, melphalan and alemtuzumab reduced intensity allogeneic stem cell transplantat in HIV-infected patient with acute myeloid leukaemia. (December 2018) - Kanellopoulos, A.; Kaparou, M.; Xenou, E.; Paneesha, S.; Kishore, B.; Lovell, R.; Holder, K.; Suhr, J.; Baker, L.; Ryan, L.; Nikolousis, E.
Allogeneic stem cell transplantation (Allo-HSCT) is sine qua non to cure high-risk acute myeloid leukaemia (AML). In spite the advent of highly active antiretroviral treatment, HIV-infected patients display a remarkable risk for haematological neoplasms such as non-Hodgkin lymphomas, Hodgkin lymphoma and acute leukaemia. Several case series have confirmed the efficacy of the autologous stem cell transplantation for the treatment of non-Hodgkin lymphomas in the HIV setting. Nonetheless, there is a paucity of data for the role of the Allo-HSCT in HIV-infected individuals with haematological malignancies. Herein, we presented the successful long-term outcome of a HIV-infected patient who received reduced intensity conditioned, matched unrelated donor transplant with alemtuzumab as graft-versus-host disease prophylaxis for therapy-related acute myeloid leukaemia. We propose that Allo-HSCT in HIV patients is safe and that alemtuzumab-based conditioning could further work to eradicate HIV in those whose donor is not CCR5 homozygous.